Critical pedagogy in an undergraduate English as a foreign language classroom in Bangladesh / Mohammad Ali Azgor Talukder - Mohammad Ali , Azgor Talukder (2017)
This study explores critical pedagogy in an undergraduate EFL classroom in Bangladesh. It focuses on the classroom practices that facilitate ‗criticality.‘ Here criticality refers to a stance that problematizes the assumptions that perpetuate injustice in society. The study also looks into the routes the learners take towards criticality and the ways language mediates the communication of criticality. As different socio-cultural contexts may influence criticality differently, the context of Bangladesh calls forth an in-depth study of criticality in the classroom context. This is a qualitative case study of critical pedagogy in an English writing course in an undergraduate classroom in Bangladesh. The course comprised of 12 two-hour classes spread out over a period of four months. The researcher played the role of a teacher-researcher. Data were collected from multiple sources namely recordings of classroom interactions of 12 classes, documents of students‘ writings, interviews with the students, and the teacher-researcher‘s post-lesson reflections. The study reveals that the role of the teacher in critical pedagogy is a complex one involving a dilemma about problematization lest it contribute to indoctrination. It also reveals that students‘ engagement in dialogue may appear different in different situations. The study also finds that in their movement of positionality towards critical stance students at first became aware of injustice as they negotiated multiple other discourses presented in the classroom and then they attempted problematization. Literature considers this movement towards criticality as othering. However, this study finds the process as fluid and recursive revealing the routes to criticality as both othering and reclaiming some of the internal discourses. As for the ways language mediates the communication of criticality, it finds a particular pattern of interrelationship of voices in the linguistic expressions that communicate criticality. Thus the study unfolds new understandings regarding critical pedagogy in the language classroom.